{Additive effect of depressed mood and vasomotor symptoms on postmenopausal insomnia.} - Zervas, I.M. Iannis M; Lambrinoudaki, Irene; Spyropoulou, Areti C A.C.; Koundi, Kalliopi L; Voussoura, Eleni; Tzavara, Chara; Verdeli, Helen; Aravantinos, Leon; Creatsa, Maria; Thomas Paparrigopoulos (Menopause (New York, N.Y.), 2009)
OBJECTIVE: The aim of this study was to investigate the role of vasomotor and mood symptoms on insomnia in postmenopausal women. METHODS: One hundred sixty-three postmenopausal women, not receiving hormone therapy, attending a menopause clinic at the University of Athens, Greece, were included in this cross-sectional study. Climacteric symptoms were assessed by Greene's scale, whereas psychological morbidity was measured by Zung Self-Assessment Depression Scale, Symptom Checklist-90-R, and Athens Insomnia Scale. RESULTS: Vasomotor symptoms were significantly associated with insomnia (P = 0.001). When depressive symptomatology was added to the logistic regression analysis, the predictive ability of the model was significantly improved as defined by the increase in the log likelihood (P < 0.001) and the increase in the area under the receiver operating characteristic curve. CONCLUSIONS: Insomnia in postmenopausal women attending a menopause clinic is related both to the effects of vasomotor symptoms and depressive symptomatology. Mood symptoms seem to affect sleep independently of vasomotor symptoms, suggesting that depression should be carefully assessed and treated in postmenopausal women with insomnia.
Keywords: Affect; Cross-Sectional Studies; Depression; Depression: complications; Female; Greece; Hot Flashes; Hot Flashes: complications; Humans; Insomnia; Logistic Models; Marital Status; menopause; Middle Aged; POSTMENOPAUSE; Postmenopause: physiology; Postmenopause: psychology; ROC Curve; Sleep Initiation and Maintenance Disorders; Sleep Initiation and Maintenance Disorders: etiolo; Vasomotor symptoms; Vasomotor System; Vasomotor System: physiopathology